142k views
0 votes
Suppose that the functions fand g are defined for all real numbers x as follows.

f(x)=x-2
g(x) = 2x+2
Write the expressions for (f-g)(x) and (f.g)(x) and evaluate (f+g)(-1).

User Luke Foust
by
4.8k points

1 Answer

5 votes

Answer:

(f-g)(x)= -x-4

(f.g)(x)= 2x^2 -2x-4

(f+g)(-1) = 3(-1) = -3

Explanation:

Hi, to answer this question we have to solve the expressions:

(f-g)(x) = x-2 -(2x+2)

(f-g)(x)= x-2 -2x-2

(f-g)(x) = -2x+x-2-2

(f-g)(x)= -x-4

(f.g)(x) = x-2 (2x+2)

(f.g)(x)= 2x^2 +2x-4x-4

(f.g)(x)= 2x^2 -2x-4

(f+g)(x)= x-2 +2x+2

(f+g)(x) = x+2x-2+2

(f+g)(x)= 3x

(f+g)(-1) = 3(-1) = -3

Feel free to ask for more if needed or if you did not understand something.

User Steve Kass
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.